2013
DOI: 10.1177/1354068813509519
|View full text |Cite|
|
Sign up to set email alerts
|

Party membership and closeness and the development of trust in political institutions

Abstract: Political parties are essential linkage mechanisms between citizens and the political system. We know less, however, about the question how this mechanism operates. While some authors assume it is sufficient that parties offer citizens ideological options about the way society should be governed, others indicate that parties provide strong ties to the political system by offering stable identities like party membership. In this analysis of the European Social Survey cumulative file (five waves, 2002-2010), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 38 publications
1
33
0
3
Order By: Relevance
“…These developments have been interpreted in contrasting ways with some observers voicing concern about their implications for democratic legitimacy given the role of parties as a key linkage mechanism between citizens and the state. When voters feel close to a political party then they are arguably more likely to feel connected to the political system as a whole (Hooghe & Kern, 2015). Furthermore, a party identification can serve as a cognitive heuristic that helps citizens to make sense of the complex political world and guides their voting decisions (Lau & Redlawsk, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These developments have been interpreted in contrasting ways with some observers voicing concern about their implications for democratic legitimacy given the role of parties as a key linkage mechanism between citizens and the state. When voters feel close to a political party then they are arguably more likely to feel connected to the political system as a whole (Hooghe & Kern, 2015). Furthermore, a party identification can serve as a cognitive heuristic that helps citizens to make sense of the complex political world and guides their voting decisions (Lau & Redlawsk, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pad institucionalnog povjerenja zadesio je i postsocijalistička društva tijekom posljednjih dvaju desetljeća, pri čemu je kontinuirano niži od onog u zapadnim društvima (Mishler i Rose, 1997;Sztompka, 1999;Badescu i Uslaner, 2003;Cattenberg i Moreno, 2006;Šalaj, 2007;Zmerli, Newton i Montero, 2007;Kukovič, 2013;Hooghe i Kern, 2013). Ipak, opadanje političkog povjerenja u postsocijalističkim društvima ne pripisuje se jača-nju vrijednosti samoizražavanja i kritičke osviještenosti građanstva prema hijerarhiziranim autoritetima karakterističnima za demokratsku političku kulturu nego nestajanju iluzija o demokraciji i razočaranju novim sustavom (Cattenberg i Moreno, 2006), potom perzistenciji kulturnih čimbenika (poput religije kao »robusne kulturne zone«) te socijalističkog naslijeđa (Inglehart i Welzel, 2005).…”
Section: Odrednice Političkog Povjerenjaunclassified
“…The political orientation of citizens provides a general framework for understanding the context. This political orientation provides a clear speech about how to understand certain political issues and what position should be taken to these issues (Hooghe & Kern, 2013). Several studies have found that citizens with a leftist orientation are more likely to participate in protest (e.g.…”
Section: Ideological Positioningmentioning
confidence: 99%
“…They provide a mechanism for identification with the political system and they aggregate their preferences (Panebianco, 1988). Political parties also provide citizens identification with relevant policy issues and their positions on those issues (Hooghe & Kern, 2013). Recent studies on the Occupy/Indignados movement have found that their participants have no clear position in relation to parties, criticizing them for being part of the system they don't trust (Manilov, 2013;Pickerill & Krinsky, 2012).…”
Section: Ideological Positioningmentioning
confidence: 99%
See 1 more Smart Citation